2011
DOI: 10.1016/j.gaitpost.2010.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Inter-limb centre of pressure symmetry during gait among stroke survivors

Abstract: The purpose of the present study was to describe the spatial-temporal parameters of the centre of pressure (COP) trajectory during the single-support phase of gait among stroke survivors and relate these parameters to the severity of sensorimotor impairment. Fifty-seven participants were asked to walk at their preferred and fast speed over a pressure sensitive mat. Outcome measures included anterior-posterior (AP) COP displacement, AP-COP velocity, medial-lateral (ML) COP variability and foot region COP time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 16 publications
2
45
0
Order By: Relevance
“…In comparison to straight paths, the COP trajectory is modulated during curved walking, as seen by the reduction in AP displacement, lateral shift in position, and greater ML variability. Similar to a previous study, S1 demonstrated poor forward progression on the paretic side and a greater difference between limbs for AP-COP displacement than S2, likely due to a greater severity in lower-limb sensorimotor control [27]. The difference between limbs for AP-COP displacement may be related to challenges in controlling stability during forward progression over the paretic limb.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…In comparison to straight paths, the COP trajectory is modulated during curved walking, as seen by the reduction in AP displacement, lateral shift in position, and greater ML variability. Similar to a previous study, S1 demonstrated poor forward progression on the paretic side and a greater difference between limbs for AP-COP displacement than S2, likely due to a greater severity in lower-limb sensorimotor control [27]. The difference between limbs for AP-COP displacement may be related to challenges in controlling stability during forward progression over the paretic limb.…”
Section: Discussionsupporting
confidence: 76%
“…Research on measuring the COP trajectory to understand neuromuscular control during walking in the stroke population has mainly focused on straight walking and gait initiation [27,33]. In comparison to straight paths, the COP trajectory is modulated during curved walking, as seen by the reduction in AP displacement, lateral shift in position, and greater ML variability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations